Ortotopik mesane yapılan sistektomide prostat korunması güvenilir bir yöntem midir? - (:unkn) unknown (My University, 2005)
Bazı araştırmacılar, radikal sistektomi sonrası kontinansına katkıda bulunacağı düşüncesiyle prostatik apeksin bırakılmasını savunmaktadır. Ancak literatürde de bildirildiği gibi radikal sistoprostatektomi kesitlerinde rastlantısal prostat kanseri tespit edilebilmekte ve bu tümörler prostat apeksinde tespit edilebilmektedir. Sonuçta, eğer cerrah prostatektomi veya uygun apikal disseksiyon yapmaz ise, geride prostat kanseri odağı bırakılabilmektedir. Bu çalışmada radikal sistoprostatektomi kesitlerinde tespit edilen rastlantısal prostat kanseri insidansı ve histomorfolojik özellikleri araştırıldı. Kliniğimizde, 1991-2004 tarihleri arasında, radikal sistoprostatektomi operasyonu uygulanan ve düzenli takip edilen toplam 34 erkek hasta araştırmaya alındı. Tüm hastalara fizik muayene (rektal muayene ile birlikte), laboratuar (prostat spesifik antijen ile birlikte) ve radyolojik inceleme uygulandı. Sadece 1 hastada şüpheli PSA değeri tespit edilirken, bu hastaya cerrahi öncesinde transrektal ultrason eşliğinde prostat biyopsisi yapıldı. Hastaların %85.4'ünde transizyonel hücreli kanser tespit edilirken, %8.8'inde skuamöz hücreli kanser, %2.9'unda adenokarsinom ve %2.9'unda küçük hücreli kanser tespit edildi. Mesane tümörlerinin sadece %10.3'ü yüzeyel mesane tümörüydü. Hastaların 11'inde (%32.4) prostat adenokarsinomu tespit edildi. Rastlantısal prostat kanseri tespit edilen hastaların yaş ortalaması 59.7 yıldı. Bu hastaların 7'sinde (%20.6) prostat adenokarsinomu evresi pT2a, 4 (%11.8) hastada pT2b olarak rapor edilirken, 2 hastada (%5.9) yüksek dereceli PIN ve 1 hastada (%2.9) düşük dereceli PIN saptandı. Rastlantısal prostat kanseri tespit edilen hastaların 3'ünde (% 27.3) prostatik apekste tümor odağı tespit edildi. Değişik çalışmalarda rastlantısal prostat kanseri insidansı %28-61 olarak bildirilmiştir. Bizim çalışmamızda da bu oran %32.4 olarak tespit edildi. Rastlantısal prostat kanseri ile yaş ve ameliyat öncesi PSA düzeyi arasında anlamlı bir ilişki tespit edilemedi. Hastaların prognozunu etkileyen ana prognostik faktörün primer mesane tümörü olduğu, prostat kanseri varlığının prognoza etkisi olmadığı gözlendi. Radikal sistektomi sırasında prostat dokusunu bütün olarak prostatik apeks korunmaksızın çıkartılmasının, onkolojik prensipler açısından önemli olduğunu düşünmekteyiz.

Introduction: Radical cystectomy is the standard treatment modality for invasive bladder cancer, and can be performed in patients with superficial bladder tumor refractory to intracavitary immuno/chemotherapy, recurrent high grade superficial bladder cancers and in the presence of carcinoma in-situ. There is a debate about prostatic dissection during radical cystoprostatectomy and neobladder in male patients. Some authors advocate leaving the prostatic apex or prostate for postoperative continence of the patient. As indicated in the literature, incidental prostate cancer can be detected in radical cystoprostatectomy specimens and this tumor can be located in the apical region of the prostate. Therefore, a prostate cancer focus could be left behind, if the surgeon does not perform prostatectomy or a proper apical dissection of the prostate. As a result some authors advocate performing prostatectomy with a wide apical resection of the prostatic apex. In this study we investigated the incidence and histomorphological properties of incidental prostate cancer in radical cystoprostatectomy specimens. Materials and Methods: A total of 34 male patients who underwent radical cystoprostatectomy with a regular follow-up in Marmara University Department of Urology between 1991 and 2004, were included to the survey. All patients had a regular physical examination (including a rectal examination), laboratory examination (including prostate specific antigen) and radiological examination. Only one patient had a suspicious PSA value and had transrectal ultrasound guided prostate biopsy before surgery. The pathology of the specimens was evaluated by the Pathology Department of Marmara University Hospital. Results: Transitional cell carcinoma was detected in 85.4% of the patients whereas 8.8% of patients had squamous cell carcinoma, 2.9% had adenocarcinoma and 2.9% had small cell carcinoma. Only 10.3% of the bladder tumors were superficial. Prostate adenocarcinoma was detected in 11 (32.4%) patients. The mean age of the patients who had incidental prostate cancer was 59.7 years. The stage of prostate cancer was pT2a in 7 (20.6%) and pT2b in 4 (11.8%) patients. There were high grade PIN in 2 patients (5.9%) and low grade PIN in 1 (2.9%) patient. In 3 patients (27.2%) with incidental prostate cancer, there was a focus in the prostatic apex. Conclusion: In different studies, the incidence of incidental prostate cancer was reported to be 28-61%. In our study we detected incidental prostate cancer in 32.4% of the patients. There was no statistical significance between the age, preoperative PSA value and the incidence of incidental prostate cancer. The prognosis of the patient was not related with the presence of incidental prostate cancer, indeed the major prognostic factor of the patients was the primary bladder tumor. Although there is no statistically significant effect of incidental prostate cancer in patients' prognosis, there is no surveillance data of the patient who has residual incidental prostate cancer after radical cystoprostatectomy. As the incidence of incidental prostate cancer in radical cystoprostatectomy seemed to be high, it is better to remove the entire prostate including the prostatic apex during radical cystoprostatectomy for oncological principles.
Is prostate sparing surgery a safe technique for radical cystectomy with orthotopic neobladder?
Keywords: Tıbbi Araştırmalar Deneysel; Onkoloji; Üroloji ve Nefroloji